Evaluasi Fungsi Kawasan Di Kota Padang - Fadillah, Rizky; Ahyuni, Ahyuni (JURNAL BUANA, 2026)
In the world of GIS (Geographic Information System), one of the makes use of of the python language is withinside the ArcGIS software made with the aid of using ESRI to create geoprocessing scripts that may run spatial evaluation features efficiently and permit automation of spatial evaluation. This studies makes a speciality of designing python programming good judgment for local features withinside the metropolis of Padang. The sort of studies used on this studies is descriptive quantitative with the aid of using studying spatial information the use of Geographic Information System (GIS). Based at the outcomes and dialogue of the studies, it may be concluded that Python can maximize the paintings of spatial evaluation thru writing scripts which can be written at the question and discipline calculate system, so that you can make the manner quicker and greater effective. The process of development emphasizes through system phases of engineering and modeling, requirements analysis, design, code generation, and testing (verification). Ultimately, performing spatial analysis on a ModelBuilder system supported by the use of Python is more efficient and effective in performing spatial analysis, and the final result is accurate depending on the use of parameters. The completed model can also be developed (updated) and implemented to perform other spatial analyzes..